Workshop Peran Generasi Milenial Dalam Meningkatkan Skill Bidang Keamanan Informasi Dan Jaringan - Anita Sindar Sinaga; Arjon Samuel Sitio; Ravindran Ravindran; Sumitra Dewi (Jurnal Pengabdian kepada Masyarakat Nusantara, 2022)
Internet activities require ethics and knowledge to understand the protection of data privacy, avoid forms of computer crime and know the forms of internet network security. Workshop activities are carried out to attract participants' interest in the subject matter of the activity. The discussion in the workshop focused on the core problems, presented systematically by the resource persons so that participants could easily understand, follow or practice. The workshop was held by demonstrating the forms and stages of information and network security through hardware and software security, personal data security, and windows operating system security. Ability to configure the information and network security on internet network devices. The partners involved are the tenth graders of Gajah Mada Padang Bulan Senior High School, Medan. The workshop participants' basic contribution is understanding and implementing data privacy security while surfing the internet and increasing students' awareness of information systems and network security skills.